Emergence of new insect-restrictive viruses in the Amazon Region - Nunes, M?rcio Roberto Teixeira (American Society for Microbiology, 2016)
The complete genome was determined for 12 viruses isolated from 8 different pools of mosquitoes (Culex sp. and Psorophora ferox) collected at Brejeira farm, Canaan dos Carajas, Para state in northern Brazil. Eight of the viruses were distantly related to Piura virus, hereafter designated as Brejeira virus; the other 4 were similar to Wallerfield virus.